The Concept of Istidraj in the Qur'an: Comparative Study of the Interpretation of Al-Imam Al-Qurtubi and Shaikh Wahbah Al-Zuhaily - Fauzi Fathur Rosi; Pajar Amirul Mu’ti (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
Happiness is one of the natural attitudes of humans when getting a lot of pleasure from Allah SWT, such as health and sustenance. However, not many of humans are correct in responding to these blessings, pleasures that are not properly addressed are termed istidraj. Istidraj is a punishment given by Allah SWT to the perpetrators of immorality in the form of worldly pleasures that seem beautiful but cause negligence in the real world. Therefore, it is necessary to be aware of istidraj as a sign of caution in order to avoid immoral acts. The phenomenon of istidraj in this study explores the concept of this in the Qur'an through the perspective of two mufasirs, namely al-Imam al-Qurtubi and Wahbah al-Zuhaily in answering 2 focuses, namely: 1. How to interpret istidraj in the Qur'an according to al-Imam al-Qurtubi and Wahbah al-Zuhaily 2. What are the similarities and differences between al-Imam al-Qurtubi and Wahbah al-Zuhaily regarding istidraj. To understand the concept of the istidraj phenomenon, this study applies a qualitative method of literature study with a comparative study approach. In this approach, the researcher compares the interpretation of al-Imam al-Qurtubi through the tafsir